Implementasi pembelajaran diferensiasi pada pembelajaran pendidikan pancasila di sekolah dasar - Dania Nurfitriani; Siti Istiyati; Fadhil Purnama Adi (Universitas Sebelas Maret, 2025)
This research aims to (1) describe the planning, (2) implementation and (3) evaluation of the application of differentiated learning in Pancasila education learning related to content strategies, processes, products and learning environments. This research includes descriptive qualitative research with a case study approach. The subjects in this research were the homeroom teacher and class IVB students at Ta'mirul Islam Elementary School, Surakarta. Data collection techniques use observation, interviews and documentation. Data validity testing techniques uses triangulation of techniques and source. The data analysis technique uses analysis from Cresswell. The research result show that the planning stages were carried out properly non-cognitive diagnostic assessment and observation, setting learning objectives preparing ATP and KKTP, preparing teaching modules and analyzing teaching modules. The implementation stages refer to content, process, product, and learning environment strategies. Content strategy is carried out with a variety of learning sources and media, process strategy is carried out by creating a learning environment that inspires enthusiasm for learning. The evaluation stages are carried out with formative and summative assessments. By implementing this differentiated learning, it has a positive impact on students, namely increasing student motivation in learning, and increasing student learning outcomes.